Care or cash? The effect of child care subsidies on student performance - Sandra E. Black; Paul J. Devereux; Katrine V. Loken; Kjell G. Salvanes (Institute for the Study of Labor (IZA), 2012)
Given the wide use of childcare subsidies across countries, it is surprising how little we know about the effect of these subsidies on children's longer run outcomes. Using a sharp discontinuity in the price of childcare in Norway, we are able to isolate the effects of childcare subsidies on both parental and student outcomes. We find very small and statistically insignificant effects of childcare subsidies on childcare utilization and parental labor force participation. Despite this, we find significant positive effect of the subsidies on children's academic performance in junior high school, suggesting the positive shock to disposable income provided by the subsidies may be helping to improve children's scholastic aptitude.
urn:nbn:de:101:1-201208175104
Keywords: I1; J1; 330; education; income subsidy; child care; Kinderbetreuung; Subvention; Wirkungsanalyse; Kinder; Bildungsniveau; Norwegen